The effect of government expenditure components towards economic growth in Malaysia / Nadzirah A Manaf - A Manaf, Nadzirah (2017)
The main purpose of this paper is to analyse the effect of government expenditure components towards economic growth in Malaysia over the period from 1970 to 2015. This study to would like to determine how the government expenditure effect on economic growth in Malaysia through its components such as military expenditure, educations expenditure and healthcare expenditure. In this study, the government expenditure has been dissagregated into development expenditure such as military expenditure, education expenditure and healthcare expenditure. This study may give some overview of policy implications to the Malaysia policymakers on optimizing the effects of government expenditure in economic growth.